Complement Terminal Pathway Activation is Associated with Organ Failure in Sepsis Patients - Ahmad FM; A Al-Binni M; Bani Hani A; Abu Abeeleh M; Abu-Humaidan AHA (Dove Medical Press, 2022)
Fatima M Ahmad,1,2 Maysaa' A Al-Binni,2 Amjad Bani Hani,3 Mahmoud Abu Abeeleh,3 Anas HA Abu-Humaidan1 1Department of Pathology, Microbiology and Forensic Medicine, School of Medicine, The University of Jordan, Amman, Jordan; 2Department of the Clinical Laboratory Sciences, School of Science, The University of Jordan, Amman, Jordan; 3Department of General Surgery, School of Medicine, The University of Jordan, Amman, JordanCorrespondence: Anas HA Abu-Humaidan Tel +962779227922Email A.abuhumaidan@ju.edu.joBackground: Complement plays a pivotal role in the immune response to infection. Several studies demonstrated complement activation in sepsis, yet little is known of the relationship of complement terminal pathway activation and the clinical characteristics of sepsis patients. Therefore, we investigated serum C5, soluble C5b-9 (sC5b-9), and soluble CD59 (sCD59) and their relation to organ failure in sepsis patients in the intensive care unit (ICU).Methods: In this prospective cohort study, all available patients admitted to the adult ICUs between June 2020 and January 2021 were included. Patients were divided into sepsis and non-sepsis groups according to the Sepsis-3 criteria, serum samples from both groups were investigated for the levels of C5, sC5b-9, and sCD59 using commercial sandwich ELISA kits.Results: We analyzed 79 serum samples, 36 were from sepsis patients. We found that sepsis patients had significantly lower C5 (83.6± 28.4 vs 104.4± 32.0 μg/mL, p = 0.004) and higher sCD59 (380.7± 170.5 vs 288.9± 92.5 ng/mL, p = 0.016). sC5b-9, although higher in sepsis patients, did not reach statistical significance (1.5± 0.8 μg/mL vs 1.3± 0.7 μg/mL, p = 0.293). Sepsis patients who died during their ICU stay had significantly higher sCD59 compared to those who survived (437.0 ± 176.7 vs 267.8 ± 79.7 ng/mL, p = 0.003, respectively). Additionally, C5 and sCD59 both correlated to SOFA score in the sepsis group (rs = − 0.44, P = 0.007 and = 0.43, P = 0.009, respectively), and a similar correlation was not found in the non-sepsis group.Discussion: In sepsis patients, levels of C5 and sCD59, but not sC5b-9, correlated to the severity of organ damage measured by SOFA. A similar correlation was not found in non-sepsis patients. This indicated that organ damage associated with sepsis led to a more pronounced terminal pathway activation than in non-sepsis patients, it also indicated the potential of using C5 and sCD59 to reflect sepsis severity.Keywords: C5, C5b-9, CD59, Sequential Organ Failure Assessment, intensive care unit